Incidence, prevalence, and severity of and risk factors for hip and groin problems in swedish male ice hockey players: a 1-season prospective cohort study - Wörner, T.; Thorborg, K.; Clarsen, B.; Eek, F. (Journal of Athletic Training, 2022)
Context: The epidemiologic focus on time loss may underestimate the true magnitude of hip and groin problems in male ice hockey players.